The Aftermath of Anti-Dumping: Are Temporary Trade Barriers Really Temporary? - Magdalene Silberberger; Anja Slany; Christian Soegaard; Frederik Stender (Open Economies Review, 2021)
A consistent finding in the literature is that anti-dumping (AD) acts as a significant barrier to bilateral trade, in particular, during the time such measures are in force. Adding to a relatively scarce empirical literature, however, we identify adverse impacts of AD which survive well beyond its revocation. More specifically, while we cannot rule out a slight post-revocation recovery, we find empirical evidence that once affected bilateral trade does not fully recover on average following revocation. We use panel data at the Harmonized System four-digit (HS4) level of aggregation to produce these results and show that they are robust to the duration of AD cases, the time of their imposition and revocation, differentiation by economic sector and the nature of imposing countries. Several explanations for our observed empirical results seem plausible, and we provide a theoretical framework which suggests our results could be driven by market exit or underinvestment of targeted firms.
Keywords: D21; F13; F14; 330; Anti-dumping; Trade protection; Trade destruction